1991
DOI: 10.1177/014107689108400111
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy in Children

Abstract: Arthroscopy was performed on the knees of 67 children aged 2–16 years with an overall clinical diagnostic accuracy of 45%. The most common clinical diagnoses were meniscal tear and patello-femoral pain and the accuracy of these diagnoses was 33% and 59% respectively. Diagnostic accuracy seemed unrelated to age. Arthroscopy led to definitive treatment which relieved symptoms in 21 (31%) of cases, revealed a diagnosis only in 43 (64%), and was non-contributory in 3 (4.5%). The procedure did not significantly hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…There are several reports on arthroscopy performed in children, but only a few dealing with acute trauma. The compatibility between the clinical diagnosis and the arthroscopic findings in younger children has varied from 18 to 70 percent (Momssy et al 1982, Ziv and Carroll 1982, Suman et al 1984, Juhl and Boe 1986, Eiskjaer and Larsen 1987, Harvell et al 1989, Hope 1991, improving in older children (Suman et al 1984), like in our study. Ligamentous tears were previously thought to be less common in children (Saddowi and Hoffman 1970, Noyes at al.…”
Section: Discussionsupporting
confidence: 67%
“…There are several reports on arthroscopy performed in children, but only a few dealing with acute trauma. The compatibility between the clinical diagnosis and the arthroscopic findings in younger children has varied from 18 to 70 percent (Momssy et al 1982, Ziv and Carroll 1982, Suman et al 1984, Juhl and Boe 1986, Eiskjaer and Larsen 1987, Harvell et al 1989, Hope 1991, improving in older children (Suman et al 1984), like in our study. Ligamentous tears were previously thought to be less common in children (Saddowi and Hoffman 1970, Noyes at al.…”
Section: Discussionsupporting
confidence: 67%
“…These studies have reported overall accuracy rates of 29% to 59% in series ranging from 28 to 285 patients. 1,7,1113,15,19,26,35,3739 Potential explanations for the relatively low accuracy of clinical examination in the diagnosis of knee disorders in children and adolescents include difficulty in obtaining an accurate history, difficulty in localizing symptoms, lack of patient cooperation and relaxation during examination, lack of recognition of significant injuries, and the more varied differential diagnoses associated with these age groups. In a recent study assessing the agreement of clinical examination with arthroscopic findings by a single experienced pediatric orthopaedic sports medicine specialist in 28 children and adolescents, 33 the overall accuracy of clinical examination (93.5%) was similar to the accuracy in this study (86.3%).…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6,8,10,14,17,18,21,24, 25,2830,42 Other studies have assessed the diagnostic performance of clinical examination of the knee by comparing clinical diagnoses with arthroscopic findings. 1,7,1113,15,19,26,35,3739 Finally, some studies have correlated diagnoses based on both MRI and clinical evaluation with arthroscopic findings. 7,22,3133…”
mentioning
confidence: 99%
“…The clinical diagnosis was confirmed by the author in 45% of cases and in 51% arthroscopy extended preliminary diagnosis with significant elements. Hence the conclusion that an indication for arthroscopy is clinically significant pathology or chronic diseases which do not react to conservative treatment (7) .…”
Section: Discussionmentioning
confidence: 99%